Inhibitory effects of leaf extract of Apama tomentosa on ovarian cancer - Lee, I.L.; Kanthimathi, M.S.; Wiart, C.; Malik, N.A.; Kuppusamy, U.R. (2008)
Crude and hexane leaf extracts of Apama tomentosa (Aristolochiaceae) showed inhibitory effect on ovarian adenocarcinoma (CaOV-3) cells cultured in vitro with IC50 of 46.13±1.09 µg/ml and 18.50±0.50 µg/ml respectively. The crude extract exerted a mild inhibitory effect on peripheral blood mononuclear cells (PBMCs). Hexane extract and palmitone did not exert any significant effect on the PBMC proliferation. Subsequent isolation of the leaf extract led to the isolation and identification of palmitone (16-hentriacontanone). This compound exhibited inhibitory effect (IC50=17.70±1.86 µg/ml) on CaOV-3 but was ineffective on PBMCs. This plant compound can potentially help to treat ovarian cancer.